Characterization of a long overlooked copper protein from methane- and ammonia-oxidizing bacteria - Oriana S. Fisher (Nature Portfolio, 2018)
Methane- and ammonia-oxidizing bacteria use the integral membrane, copper-dependent enzymes particulate methane monooxygenase (pMMO) and ammonia monooxygenase (AMO) to oxidize methane and ammonia. Here the authors structurally characterize the copper-binding protein PmoD, which contains an unusual CuA site and their genetic analyses strongly support a pMMO and AMO related function of PmoD.